Contemporary Confucianism in Thought and Action - Alitto, Guy.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This volume focuses on contemporary Confucianism, and collects essays by famous sinologists such as Guy Alitto, John Makeham, Tse-ki Hon and others. The content is divided into three sections – addressing the “theory” and “practice” of contemporary Confucianism, as well as how the two relate to each other – to provide readers a more meaningful understanding of contemporary Confucianism and Chinese culture. In 1921, at the height of the New Culture Movement’s iconoclastic attack on Confucius, Liang Shuming (梁漱溟) fatefully predicted that in fact the future world culture would be Confucian. Over the nine decades that followed, Liang’s reputation and the fortunes of Confucianism in China rose and fell together. So, readers may be interested in the question whether it is possible that a reconstituted “Confucianism” might yet become China’s spiritual mainstream and a major constituent of world culture.
Introduction: Theory and Practice in Contemporary Confucianism -- Some Historical and Methodological Reflections on Ruxue in Contemporary China -- From Culture to Cultural Nationalism: A Study of New Confucianism of the 1980s and 1990s -- A Study on Pre-Qin Confucian Scholars’ Environmental Ethics -- On Confucian Constitutionalism -- Building a Loho Homeland with Traditional Wisdom -- Modernizing Tradition or Restoring Antiquity as Confucian Alternatives: A View from Reading Wedding Rituals in Contemporary China -- Liang Shuming: a Lifelong Activist -- Confucianism as the religion for our present time -- Liang Shuming’s Conception of Democracy -- Humankind Must Know Itself.
Keywords: Philosophy, Asian; Cultural studies; Non-Western Philosophy; Cultural Studies